Analisis Kelayakan Buku Ajar Milenial Berbasis Augmented Reality (AR) sebagai Media Pembelajaran Teks Prosedur di Magelang - Theresia Pinaka Ratna Ning Hapsari; Ayu Wulandari (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This research was motivated by a problem in learning Indonesian in grade VII SMP with the material of Procedure Text. To overcome this, a learning media was made using technology to facilitate the distance learning process or independent learning. This study aims to describe the validity or feasibility value of millennial textbooks based on Augmented Reality technology used in learning Indonesian at the Junior High School level (SMP) in Procedure Text material. The Millennial Textbook is named The Magic Book, which is how it works using AR technology by displaying images on the book as well as 3D animation on Android-based devices. This research is a research and development or Research and Development (RnD) using the theory of Borg & Gall which contains 3 major steps, namely design, testing, evaluation. This article contains validation tests from media experts and material experts to test the feasibility value of developed textbooks and limited field trials for seventh grade students at the junior high school level in Magelang City. The result of this feasibility test is that the material expert gives an assessment score of 122 from a maximum score of 130 or equivalent to 93.8% eligibility in a valid or suitable category for use in learning. The media expert gave an assessment score of 84 out of a maximum score of 90 or equivalent to 93.3% in the valid or feasible category for use as a medium in the learning process. The results of the field trial stated that the Magic Book was categorized as valid and feasible to be applied in teaching procedural texts for seventh grade students of SMP in Magelang.